Mobbing as a problem in management ethics - Kowal, Jolanta; Gwiazda-Sawicka, Grażyna (Annales. Etyka w Życiu Gospodarczym, 2019)
A positive company image and its good reputation are usually results of ethical and honest behaviour towards employees and may improve competitiveness, increase profits, customer satisfaction, and create new job jobs. However, it often occurs in dynamically developing firms where ethical norms are not kept and this process can be seen in the lack of equal chances to get a job – people without connections remain without work. According to research, mobbing is a very serious problem. Psychological terror or mobbing in work life involves hostile and unethical communication that is conducted in a systematic manner by one or more individuals, mainly toward one individual, who, due to mobbing, is pushed into a helpless and defenceless position and held there by means of continuing mobbing activities. These actions occur on a very frequent basis (statistical definition: at least once a week) and over a long period (statistical definition: at least six months’ duration). Because of the high frequency and long duration of hostile behaviour, this maltreatment results in considerable mental, psychosomatic, and social misery.